Development of grammaticality and sentence complexity in monolingual Spanish-speaking children with specific language impairment: An exploratory study - Carmen Julia Coloma; Claudia Araya; Camilo Quezada; María Mercedes Pavez; Carlos Álvarez; Mariangela Maggiolo (Sintagma, 2019)
This study inspects the development of grammaticality and sentence complexity in Spanish-speaking children with specific language impairment (SLI). Forty-seven children were grouped following age (4-5 and 6-7) and diagnostics (SLI and Typical Language Development, TLD). Children’s oral narratives were analyzed considering grammaticality and sentence complexity. Results showed that children with SLI and TLD children follow a similar developmental pattern, both in grammaticality and sentence complexity. However, although the sentence complexity of children with SLI is similar to the sentence complexity of children with TLD, children with SLI are more ungrammatical than children with TLD. Finally, correlation between complex sentences and ungrammatical sentences was found to evolve differently when considering children with SLI and children with TLD.